Role of Collaboration in English Teacher Education: A Narrative Inquiry - Bohara, Nirajan; Awasthi, Jai Raj (Exploration अन्वेषण, 2026)
The study was conducted within the ELT (English Language Teaching) context of Nepal with experienced teachers as they implemented collaboration in teaching practices and bridged gaps in collaborative construction of educational growth. This paper explores the contribution of collaboration in the career growth of English teaching professionals. I employed narrative inquiry, and a semi-structured interview was administered to get their subjective perspectives. I implemented Vygotsky’s sociocultural theory (SCT) to view social context, reflective practice, group work, scaffolding, and autonomous exploration in learning mode. Vygotsky’s social development theory indicates that interpersonal communication can directly moderate a pupil’s reasoning and comprehension skills in the ELT milieu of Nepal. The interpretivism paradigm shaded the nuances of a robust and context-sensitive approach. Five secondary-level English teachers were selected for the paper, and a purposive sampling method was chosen under the criteria of experience, characteristics, and in-depth knowledge in the role of collaboration. Findings were inconsistencies in group members’ involvement, reflective practice in the form of collaboration, and autonomy as a teacher’s professional development. The implications highlighted the significant shift in the pedagogical approach, identity, and weaknesses faced by teachers in educational domains, as well as their professional growth in collaborative settings. Collaborative learning fosters the confidence and progressive outcomes of learners in education.